A historical-materialist reading of Genesis 1-4 - Naiweld, Ron, author.
1 online resource
Keywords: "This book offers a historical-materialist reading of the opening chapters of the book of Genesis, in an attempt to revive their potential to engage people in truthful discussions about power and pleasure. For the past two millennia, biblical stories have been told and discussed in countless settings; whether one lives in Europe or in a country that was colonized by Europeans, the biblical symbolic universe remains present. This book offers a method to explore the social and political meanings of its most theological content, by visiting two historical settings in which biblical modes of expression intersected with the demands of an economic-political process: Jerusalem and its province during the Persian period (5th-4th centuries BCE), and Brazil of the early colonial period (16th century CE). Though distant in time and space, both were moments of comparable transformation - individuals with financial resources and military power arrived from the East to seize control over lands and means of production, subjugating the population to a distant king. By turning to these two historical settings, Naiweld examines how the narratives of Genesis resonated in these environments, how they were used to legitimize imperial power structures, and how they opened these structures to scrutiny. The volume is part of a larger trend of reading the Bible with a historical-materialist approach that allows us to grasp the power of its symbolic universe to inspire both utopia and barbarism, especially in colonial contexts. This book is suitable for students and scholars interested in the biblical symbolic universe and Jewish and Christian history. It is also of interest to those working on the history of Brazil, comparative literature, and the intersection of religion, economy, and politics"--